# Homework Help: E integration

1. Mar 1, 2004

### tandoorichicken

how do i do
$$\int_{0}^{\ln 2} e^{-2x} \,dx$$
?

2. Mar 1, 2004

Try a substitution of u = -2x. Don't forget to convert the boundaries of integration.

3. Mar 1, 2004

### himanshu121

Formula : $$\int e^{ax}dx= \frac{e^{ax}}{a}+c$$

Last edited: Mar 1, 2004
4. Mar 1, 2004

Figured since himanshu threw out a formula from nowhere, I'd go ahead and derive it. I know I always hated formulas from nowhere.

$$\int_a^b e^{\alpha x}\,dx$$
make the substitution $u = \alpha x$. Therefore, $du = \alpha dx$.
$$\int_a^b e^{\alpha x}\,dx = \int_{a'}^{b'} e^{u}\frac{du}{\alpha} = \frac{1}{\alpha} \int_{a'}^{b'} e^{u}\,du$$
$$\frac{1}{\alpha} \int_{a'}^{b'} e^u\,du = \frac{1}{\alpha} e^u \Big|^{b'}_{a'} = \frac{1}{\alpha} e^{\alpha x} \Big|^b_a = \frac{1}{\alpha}(e^{\alpha b} - e^{\alpha a})$$

Last edited: Mar 1, 2004
5. Mar 1, 2004

Just a note: The constant of integration is superfluous in a definite integral, such as this problem. It just cancels itself out at the end anyway.

6. Mar 2, 2004

### himanshu121

Firstly i wrote it in the form of indefinite integral so from the rul;e i wrote c now u c y i wrote c

it is not from nowhere
$$\frac{d e^{ax}}{dx}= ae^{ax}$$

Now rearrange u will get

$$\int e^{ax}dx= \frac{e^{ax}}{a}+c$$